2000
DOI: 10.1021/la9913250
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c at Model Membrane Surfaces:  Exploration via Second Harmonic Generation-Circular Dichroism and Surface-Enhanced Resonance Raman Spectroscopy

Abstract: The novel nonlinear optical method of second harmonic generation-circular dichroism (SHG-CD) has been used to follow the adsorption and redox properties of a peripheral membrane protein, horse heart cytochrome c, adsorbed at several model membrane surfaces. The SHG-CD response is shown to be affected by the oxidation state of the heme within surface-adsorbed cytochrome c, as is consistent with the sensitivity of SHG to the chirality of the heme. SHG-CD measurements show that adsorbed cytochrome c is reducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 36 publications
(83 reference statements)
0
28
0
Order By: Relevance
“…SHG-CD has also been used, together with a surface-enhanced resonance Raman study, to monitor the oxidation state of cytochrome c adsorbed on model membranes surfaces. 72 SHG-CD was shown to be a particularly sensitive probe of the redox state of the heme group, which is known to be essential for the electron transfer process that occurs in cytochrome c. Simpson and co-workers used chiral SHG experiments to observe the dynamics of protein binding (bovine serum albumin) to a surface. 73 Their experimental results are shown in Figure 7.…”
Section: Surface Nonlinear Opticsmentioning
confidence: 99%
“…SHG-CD has also been used, together with a surface-enhanced resonance Raman study, to monitor the oxidation state of cytochrome c adsorbed on model membranes surfaces. 72 SHG-CD was shown to be a particularly sensitive probe of the redox state of the heme group, which is known to be essential for the electron transfer process that occurs in cytochrome c. Simpson and co-workers used chiral SHG experiments to observe the dynamics of protein binding (bovine serum albumin) to a surface. 73 Their experimental results are shown in Figure 7.…”
Section: Surface Nonlinear Opticsmentioning
confidence: 99%
“…Except for the modulation of cellular interactions, the orientation and conformation of proteins adsorbed onto a material surface is critical for cell integrins to recognize specific sites, which may initialize diverse signaling events. It has been widely believed that proteins undergo some conformational change when adsorbed on surfaces, with the help of sum frequency generation vibrational spectroscopy, time‐of‐flight secondary ion mass spectrometry, and second harmonic generation‐circular dichroism . It has been observed that proteins adsorbed on hydrophobic surfaces generally undergo structural rearrangement such that nonpolar amino acids interact preferentially with the surfaces, which gives rise to strong interfacial interactions and irreversible adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…However, it can probe the chirality of anisotropic systems such as chiral surfaces, as first demonstrated by Hicks group [8,9,10,11,12]. Reviews on SHG as a probe for surface chirality can be found in references [13,14,15].…”
Section: Sum-frequency Generation As a Probe Of Chiralitymentioning
confidence: 99%
“…As a result, SFG has higher sensitivity and has been used to obtain optically active electronic and vibrational spectra of a monolayer of chiral molecules [19,23]. SHG, although forbidden in chiral liquids, has been shown by Hicks et al to be able to probe the chirality of a monolayer [8,9,10,11,12].…”
Section: Sum-frequency Vibrational Spectroscopy (Sfvs) Of Achiral Intmentioning
confidence: 99%
See 1 more Smart Citation